The Realisation of the descriptive and iconographic plains in the „Viva!” biweekly - Szybalska-Taraszkiewicz, Mariola (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2013)
The article discusses the problems of the family presented in the „Viva!” biweekly. Due to the character of the magazine, the families of Polish and international celebrities from the worlds of culture, media, and politics are the main focus of attention. The internal and public lives of these families are presented, along with their values and their internalisation through action.
Keywords: family; celebrity; values; Viva